Pairs trading : strategy refinements - Magalhães, Diogo António Ribeiro (2023)
In this dissertation, we apply the pairs trading strategy, which was originally presented by Nunzio Tartaglia in the mid-80’s, for the period between 2010 and 2020, to the stock’s constituents of the S&P500. We replicated the strategy used by Gatev et al. (2006), with some differences, and our trading strategy obtained an average 6-month excess return of 13.133% and a total return of 262.658%. The strategy also proved to have a significantly better performance when the markets were declining. This study focused on discovering if the performance of the strategy would be positive in different industries. With that in mind, we created portfolios with the top 5 pairs of stocks of each industry and track the results obtained. Besides that, we applied stop losses strategies in order to refine our strategy and decrease the risk associated with the trades. Our results show that the strategy might not be applied to all of the industry as there are portfolios that presented relatively high losses and that the implementation of a stop loss can improve the performance.